Webinar dan Workshop Pelatihan Pembuatan Video Promosi Berbasis Artificial Intelligence Menggunakan Lumina AI Bagi Pelaku UMKM di DKI Jakarta - Yana Adharani; Muhammad Hanif Abdillah; Givary, Muhammad Linggar; Muhammad Fikri Dwi Saputra; Zaky Yusuf Ajindra; Muhammad Nasirul Haq; Rully Mujiastuti; Popy Meilina; Sitti Nurbaya Ambo; Rita Dewi Risanty (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs) contribute 61.07% to Indonesia’s gross domestic product, yet many remain constrained in producing competitive digital promotional content due to limitations in cost, time, and technical skills. This community service program aimed to improve MSME actors’ capacity to utilise generative artificial intelligence, specifically Lumina AI, in creating promotional images and short videos independently. The activity was conducted on 18 July 2026 at the Artificial Intelligence Laboratory, Faculty of Engineering, Universitas Muhammadiyah Jakarta, in partnership with the MSME Division of the Muhammadiyah Regional Board of DKI Jakarta, involving 25 participants from the culinary, handicraft, and service sectors. The method integrated lecture, demonstration, guided practice, and individual mentoring, structured around a five-part training module. Effectiveness was assessed through pretest, posttest, and evaluation of participants’ outputs. All participants successfully produced at least one promotional image and one short promotional video from their own product photographs. The mean score moved from 92.59 to 92.65 out of 105, while the minimum score increased from 35 to 42 and the number of participants achieving the maximum score rose, indicating an equalisation of understanding rather than an increase in average performance. These findings suggest that short, practice-oriented training accompanied by individual mentoring effec